DAKWAH TERAPEUTIK (Sebuah Pengantar) - Nazirman Nazirman (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Therapeutic is a popular term among medical world that is oriented treatment or recovery process psychiatric conditions. This term will exist in other professions, including Dakwah. Dakwah is not just an attempt to invite to goodness but also to create conditions that encouraged people trying to maintain the mental stability and spiritual nursing through the application and realization of the Islamic teachings in their life. Problem issues in this theme is how to format, techniques and therapeutic dakwah procedures work that needs to be understood by a da`i.